Social platform content marketing strategies for sustainable sales growth of local specialty green agricultural products - Moran Fan; Chunling Zhang; Chunling Zhang (Frontiers in Sustainable Food Systems, 2025)
IntroductionSocial platform content marketing, with its extensive reach and precise targeting, has gradually become a key driver in promoting the sustainable sales growth of local specialty green agricultural products.MethodsThis study examines local specialty green agricultural products in China, using Sichuan Pujiang dekopon as the research subject. Based on the ELM theoretical model, it analyzes 232 TikTok accounts selling this product. By utilizing sales data, the study applies a combination of PLS-SEM and fsQCA to explore the impact mechanism of content marketing on sustainable sales growth and constructs pathways and strategies to enhancing the sustainable sales growth of local specialty green agricultural products.ResultsThe results show that product trust evaluations, source credibility, and content flow experience significantly contribute to sales growth, while account trust evaluations, product trust evaluations, source credibility, and content flow experience positively influence relationship commitment. Notably, account trust evaluation did not significantly affect purchase behavior, suggesting a rational decision-making process and a broken conversion path from account trust to action in local specialty agricultural products consumption. fsQCA reveals the complex causal relationships between the central route and peripheral route in shaping the pathways to sustainable sales growth.DiscussionThe findings provide guidance for local specialty green agricultural products in leveraging social platform content marketing, ensuring their sustainable sales growth.